(untitled) (Advances in Applied Mathematics and Mechanics, 2011)
In this paper, a numerical method employing a finite difference technique is used for an investigation of viscous, incompressible fluid flow in a tube with absorbing wall and slowly varying cross-section. The effect of fluid absorption through permeable wall is accounted by prescribing flux as a function of axial distance. The method is not restricted by the parameters in the problem such as wave number, permeability parameter, amplitude ratio and Reynolds number. The effects of these parameters on the radial velocity and mean pressure drop are studied and the results are presented graphically. Comparison is also made between the results obtained by perturbation method of solution and present approach.